CULTURAL DIFFERENCES IN UNDERSTANDING ENGLISH PHRASEOLOGICAL UNITS - Rakhimova Gavkhar Jamshid kizi (Economics, management, and digital innovation in education: contemporary trends and approaches, 2025)
This paper explores how cultural differences influence the comprehension and interpretation of English idioms. Idioms are deeply rooted in the history, traditions, and values of English-speaking societies, which often makes them challenging for non-native speakers. By analyzing theoretical perspectives and practical examples, this study demonstrates the role of culture in idiomatic meaning and provides insights into translation and language teaching.